2008
DOI: 10.1186/1472-6882-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Treatments of pelvic girdle pain in pregnant women: adverse effects of standard treatment, acupuncture and stabilising exercises on the pregnancy, mother, delivery and the fetus/neonate

Abstract: Background: Previous publications indicate that acupuncture is efficient for the treatment of pelvic girdle pain, PGP, in pregnant women. However, the use of acupuncture for PGP is rare due to insufficient documentation of adverse effects of this treatment in this specific condition. The aim of the present work was to assess adverse effects of acupuncture on the pregnancy, mother, delivery and the fetus/neonate in comparison with women that received stabilising exercises as adjunct to standard treatment or sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 55 publications
0
75
0
Order By: Relevance
“…As to the exercises that were supervised by different therapists, previous studies found that these strategies were efficient for pregnancy low back and pelvic pain (8)(9)(10). The importance of supervision during the exercises for the treatment and prevention of low back pain is also emphasized in studies that did not focus solely on pregnant women (45,46).…”
Section: Group and Individual Protocols With Or Without Supervisionmentioning
confidence: 99%
See 3 more Smart Citations
“…As to the exercises that were supervised by different therapists, previous studies found that these strategies were efficient for pregnancy low back and pelvic pain (8)(9)(10). The importance of supervision during the exercises for the treatment and prevention of low back pain is also emphasized in studies that did not focus solely on pregnant women (45,46).…”
Section: Group and Individual Protocols With Or Without Supervisionmentioning
confidence: 99%
“…The studies by Garashabi et al (9) and Schim et al (26) found a reduction in the intensity of low back and conflicting evidence, because they differed as to the duration of the interventions, the effects on pain intensity and on functional limitations; on the study that found positive results (37), the duration of the intervention was only a week. Other studies (8,11) indicate that specific stabilization exercises for strengthening the muscles of the pelvic girdle can be effective in the treatment of pregnancy pelvic pain, with relatively short interventions (six weeks).…”
Section: Duration and Frequency Of The Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2008 study 34 focused on adverse events in 386 pregnant women randomized to one of four pelvic-pain treatments, including acupuncture. No adverse maternal or fetal medical events were reported, but the acupuncture group had the highest rate of minor maternal complaints; most related to mild pain at the site of needling.…”
Section: Reports Of Adverse Events In the 28-year Review Periodmentioning
confidence: 99%